HIGHER EDUCATION FOR PUBLIC ACCOUNTANTS. - Webster, Norman E. (The Accounting Review, 1938)
Abstract The article focuses on four matters related to higher education for public accountants, reasons for the change nearly nine years ago in the New York law; standards for judging the suitability of a school's offerings; and collegiate education as the basis for admission to CPA examinations from the points of view of the examiner and of the professional accountant. New York State does not have a board of accountancy such as has been created in most other U.S. states. The control of certified public accountancy in New York is lodged in The University of the State of New York, which is not an educational institution but is an administrative body. At its head are the Regents of the University, now twelve in number, who serve without compensation, and one of whom is elected each year by joint ballot of the two Houses of the Legislature. Responsibility and authority for the administration of the CPA Law in New York rest with the Regents, but for the execution of the policies which they adopt, the Education Law provides four agencies, namely, the Education Department which, as to accountancy, acts principally through the Assistant Commissioner for Higher Education and the divisions of professional education and higher education; the Council on Accountancy, an advisory body of five eminent certified public accountants, who serve without compensation; the Grievance Committee, consisting of ten certified public accountants and the Board of Certified Public Accountant Examiners. Such a cumbersome distribution of responsibilities results in delayed action upon important matters.